ASSESSMENT OF TWO OR MORE ANTIBIOTICS REGIMEN VERSUS ONE OR NO ANTIBIOTIC REGIMEN IN POST-OPERATIVE SURGERY - B., Mihirkumar; ASHLEYS.; S., Nawaz; G., Surekha; Paarakh, Padmaa M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Surgical site infections [SSI] are the leading cause of hospital-acquired infections. The objective of this study was to evaluate whether surgical site infections can be reduced with two or more antibiotics regimen versus one or no antibiotic regimen in post-operative surgery. Methods: The patients were grouped into 2 groups. Group A (two or more antibiotics regimen) and Group B (one or no antibiotic regimen). Then the patients were followed on 1st, 2nd, 3rd and 4th week respectively after surgery to check for any surgical site infection by direct interviewing the patients. Results: The overall surgical site infection rate was 48.3 % (58 out of 120 patients). However, this study was more dominated by female patients–there were 63% female patients compared to 37 % male patients enrolled in this study. Also, the post-operative surgical site infection was comparatively observed more in female patients than in male. General surgery department too had many gynaecology related patients followed by Orthopaedic and Endocrinology surgeries. Results revealed that the patients in Group A (Two or more antibiotics) had significantly lower number of surgical site infections when compared with Group B (One or no antibiotics) with p<0.001. Conclusion: Our study concludes that patients receiving two or more antibiotics had significantly less number of post-operative surgical site infections when compared to patients receiving one or no antibiotics and following two or more antibiotics can reduce the excess hospital cost.